Multiple Intelligences in Prospective Biology Teachers and Their Role in Self-Awareness and Learning Strategies - Nanda Eska Anugrah Nasution (Fakultas Tarbiyah Ilmu Keguruan Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2025)
This study explores the multiple intelligences of prospective teachers and their role in self-awareness and learning strategies, with a focus on second-year students in the Biology Education program at UIN Kiai Haji Achmad Siddiq Jember. Using a qualitative descriptive research design, the study gathered data from 44 voluntarily participating students through multiple intelligence assessments, self-reflection questionnaires, semi-structured interviews, and Focus Group Discussions. The findings reveal that the most dominant intelligence type among respondents was intrapersonal intelligence (25%, n=11), followed by naturalistic intelligence (20.5%, n=9), and then musical intelligence (18.2%, n=8). This was followed by four intelligence types with the same percentage (6.8%, n=3), namely bodily-kinesthetic intelligence, spatial-visual intelligence, interpersonal intelligence, and logical-mathematical intelligence. Lastly, two intelligence types had the same number of respondents (4.5%, n=2), namely existential intelligence and linguistic intelligence. Students with high intrapersonal intelligence exhibited strong self-reflection and independent learning tendencies, while those with naturalistic intelligence preferred experiential, nature-based learning. This study highlights the importance of self-awareness in optimizing learning strategies and suggests that teacher education programs incorporate multiple intelligence-based approaches to support diverse learning styles.